2014
DOI: 10.1002/jso.23701
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous microwave ablation of stage I medically inoperable non‐small cell lung cancer: Clinical evaluation of 47 cases

Abstract: Purpose To retrospectively evaluate safety and effectiveness of CT-guided percutaneous microwave ablation (MWA) in 47 patients with medically inoperable stage I peripheral non-small cell lung cancer (NSCLC). Methods From February 2008 to October 2012, 47 patients with stage I medically inoperable NSCLC were treated in 47 MWA sessions. The clinical outcomes were evaluated. Complications after MWA were also summarized. Results At a median follow-up period of 30 months, the median time to the first recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 23 publications
9
80
2
Order By: Relevance
“…In general, the ablation power selected was 60–70 W and the ablative duration ranged from 4 to 8 minutes as decribed previously (1415). For tumors larger than 3.5 cm, ablation was performed with 2 antennas (14151617). Immediately after the MWA procedure, CT scanning was performed again to evaluate the tumor size, tumor morphology, and the status of adjacent organs.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the ablation power selected was 60–70 W and the ablative duration ranged from 4 to 8 minutes as decribed previously (1415). For tumors larger than 3.5 cm, ablation was performed with 2 antennas (14151617). Immediately after the MWA procedure, CT scanning was performed again to evaluate the tumor size, tumor morphology, and the status of adjacent organs.…”
Section: Methodsmentioning
confidence: 99%
“…Pain can be encountered after 2 -27.6 % of MWA ablations (▶ Table 1) [1,3,8,12]. Generally, the severity is mild to moderate, and it persists for a few days to a few weeks.…”
Section: Pain and Chest Wall Damagementioning
confidence: 99%
“…Intraparenchymal hemorrhages occur in 6 -10 % of MWAs and lead to hemoptysis in 0 -7 % of cases [2,3,16,22]. Yang et al reported a hemoptysis rate as high as 36 % [12]. These rates have been reported to be higher after RFA with 3 -9 % resulting in hemoptysis and an almost double in hemorrhage [54].…”
Section: Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Non-surgical therapeutics are current alternatives, including stereotactic body radiation therapy (SBRT) (2-9), CT-guided percutaneous radiofrequency ablation (10-14) and bronchoscopic laser therapy (15, 16). New techniques such as CT-guided percutaneous microwave (17) and cryoablation (18) are under investigation as well. However, limitations still exist for each modality.…”
Section: Introductionmentioning
confidence: 99%